Sustainable Livelihood Strategies for Women Agripreneur Resilience In East Java - Maulida, Dwi Laila; Sari, Putri Nurmalita; Hariputra, Akbar; Widayanti, Annisa Vira (Kadiri University - Faculty of Agriculture, 2025)
Women agripreneurs in East Java are critical in supporting household income and contributing to local economic development, especially in rural and vulnerable areas. However, they often face challenges, including limited resource access, fluctuating markets, and external shocks. This study aims to analyze the implementation of sustainable livelihood strategies to enhance the resilience of women agripreneurs and examine the mediating role of innovation capability in strengthening resilience amidst digital socio-economic challenges. Using the Sustainable Livelihood Framework (SLF), this research explores five key pentagonal assets: human, social, natural, physical, and economic capital. A quantitative method was applied through a survey of 70 women agripreneurs across several regions in East Java. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and VUCA to develop business resilience strategies. The results showed that all five capital assets significantly influence agripreneurial resilience, with social and economic capital playing the most dominant roles. This finding underscores the importance of integrated, asset-based strategies to strengthen women’s adaptive capacity and business sustainability. Meanwhile, Innovative capability does not mediate the sustainable livelihood and resilience strategy. Based on VUCA, the study recommends targeted policies and support programs that enhance women's access to resources, networks, and entrepreneurial skills to build more resilient and inclusive local economies.